Construction of Resource-based City Innovation Ecosystem - Huo, Dongxia; Liu, Huimin (International Journal Fine Arts and Creative Innovation, 2024)
Based on the viewpoint of innovation ecosystem and regional innovation system,this topic constructs the models of four subsystems:innovation operation (university technology enterprises, industrial enterprises above Designated Size), innovation assistance (intermediary institutions, government), innovation R & D (Research and development institutions, universities) and innovation environment (social, natural, economic and basic environment), study the construction of innovation ecosystem in resource-based cities. Through the empirical analysis of the construction of innovation ecosystem in Xinzhou of China. This paper obtains the key points of Xinzhou in the construction of innovation ecosystem, obtains the weight of model indicators by using statistical software, captures the features of the construction of innovation ecosystem in resource-based cities, and offers a proposal for the development sustainability of resource-based cities.